Defects and structural changes of graphite-rich media subjected to low-level neutron doses for radiation dosimetry - Khandaker, Mayeen Uddin *; Siti Nurasiah, Mat Nawi *; Abdul Sani, S.F.; Abdul Karim, Julia; Almugren, K.S.; Bradley, D. A. * (Elsevier, 2022)
Using commercially available, 0.3 mm thick rod-shaped, highly uniform 2B and HB grade polymer pencil lead graphite (PPLG), and subjected to a low-level neutron dose range of 2–10 Gy, a comprehensive understanding of radiation-induced effects have been achieved. The thermoluminescence (TL) and photoluminescence (PL) dose dependency, as well as changes in Raman spectroscopic characteristics, have been studied in order to understand the nature and distribution of defects in its crystal lattice structures that produce the luminescence signal. The atomic spacing, lattice constant, and the degree of structural order of the irradiated samples have been the primary focuses of the X-ray diffraction (XRD) study, which has then been followed by crystallite size calculations. The findings make it abundantly evident that neutron irradiation of different doses leads to some structural alteration in the studied sample at the microscopic level. Within the investigated dose range, all of the samples displayed an excellent linear response, with the sensitivity of the 2B grade PPLG being significantly higher than that of the HB. The findings show that the PPLG can be employed as a dosimetric medium for neutron radiation field. PPLG can provide a low-cost, highly effective system for researching radiation-driven changes in carbon, and all results anticipate 2B grade of PPLG to be a valuable material for new generation radiation dosimetry.